CREATION OF TOPOLOGY OF PRINTED BOARDS USING PHOTOPOLYMER ADITIVE TECHNOLOGIES OF 3D PRINTING - Невлюдов, Ігор Шакирович; Разумов-Фризюк, Євгеній Анатолійович; Нікітін, Дмитро Олександрович; Близнюк, Данило Сергійович; Стрілець, Роман Євгенійович (Problems of Friction and Wear, 2021)
The process of boards making using photolithography technology is time consuming and the creation of stencils requires additional costs of materials and equipment, which does not allow quickly adjust production to create new products and the lack of such flexibility is a significant disadvantage. One of the ways to solve these problems is to develop methods for adapting and optimizing the technological parameters of topology exposure the PCB without resistive films. The research object is the process of exposing topological images of printed circuit boards. The research subject is the technological parameters of SLA and DLP for exposing the topology of printed circuit boards. This work purpose is to develop methods for adapting and optimizing the PCB topology exposure technological parameters without resistive films, by using additive technologies of 3D printing. To achieve this goal it is necessary to solve the following tasks: to assess the possibilities of traditional technologies for the production of printed circuit boards; to analyze modern methods of 3D printing with photopolymer resins; to conduct experimental studies and on their basis to build a correlation-regression model of the influence of technological parameters of printing on the preservation of the initial geometric dimensions of the topology of printed conductors. In solving the problems, the methodology of conducting basic linear regression analysis of exposure parameters in the IBM SPSS Statistics program was used. Conclusions: experiments show that when using the technology of photopolymer 3D printing, it is possible to transfer the image of the topology to the PCB, combining the processes of photoresist and exposure of the topology simultaneously in one installation. During the experiment, in contrast to the results of the use of classical photoresist films, good polymerized photopolymer adhesion to the surface of the PCB workpiece was observed, as a result of which etching of the track ends was avoided during chemical etching. In further research, it will be possible to include additional factors in the model and build a more accurate regression model, which can be used in the development of software for 3D-exonization of PCB.